Cellular immune response in dairy cattle naturally infected with Fasciola hepatica in Cajamarca, Peru - Silva-Díaz, Heber (2015)
Fasciolosis caused by Fasciola hepatica is an important parasitic disease of livestock in many countries. In Cajamarca, Peru, prevalence rates above 80% are reported in dairy cattle. The aim of the study was to assess the proliferative capacity and expression of cytokines (IFN-γ and IL-4) in peripheral blood mononuclear cells from cows and calves against nonspecific phytohemagglutinin and specific excretory-secretory antigens from immature and mature stages of F. hepatica. The proliferative capacity was determined by in vitro lymphocyte proliferation and the cytokine expression was evaluated in cell culture supernatants by ELISA. Cows infected with F. hepatica showed a decreased capacity to respond against nonspecific and specific proliferative stimulus. In the cytokine profile against specific stimulus, IFN-γ expression was low while IL-4 response was high, indicating that the response remains polarized towards a TH2 type response. Naturally infected calves expressed higher IFN-γ levels compared to cows, with a similar expression of IL-4 between both groups of animals. No differences were observed in the immune response to antigens of immature and mature stages of the parasite. The results show an immunomodulatory response in adult animals that are naturally infected with F. hepatica as the disease progresses.